The mechanism of sulfidation roasting pretreatment of cerussite for enhanced flotation behavior - Yu Miao; Wanting Yang; Xuemin Ding; Jiarui Min; Bao Guo; Xiangxiang Chen; Chun Yu (Chemical Engineering Journal Advances)
Lead is an indispensable non-ferrous metal for industrial development. As primary galena(PbS) resources are being exhausted, the utilization of lead oxide ore resources have become increasingly important. Compared with the conventional lead oxide surface sulfidation flotation method by NaHS dosing in the pulp, the roasting sulfidation pre-treatment method has the characteristics of high efficiency and suitable for various types of ores. In this paper, we firstly demonstrate that pyrite(FeS2) can provide a sulfurous atmosphere to convert cerussite(PbCO3) into galena(PbS) through thermodynamic calculations. Then, the reaction conditions were optimized through the roasting sulfidation conditions such as the contact mode, time and temperature of the reaction, and the sulfidation mechanism of cerussite at high temperature roasting was studied by using XRF, XRD, SEM and XPS. It was clarified that the sulfidation of cerussite was progressed by reacting with sulfur-based atmosphere from the surface layer to form PbS, and then gradually penetrating into the inner layer until PbS was completely generated, and the recovery rate was increased from 14.95 % to >80 % after optimization.